The Effectiveness Of Song On Increasing Student Motivation For Listening Comprehension In SMA 2 Langowan - Talumewo, Avelio Jeremi; Liando, Nihta V.F; Rombepajung, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
An action research project is this capstone project. The following problem statement serves to confine the debate in this study: "How can students enhance their motivation for listening comprehension and Finding out whether teaching English through song improves students' achievement is the main goal of the research. Teachers of English as a Second Language (ESL) at SMA N 2 Langowan, in particular, may benefit from the study's findings if they decide to incorporate musical elements into their lessons.Thus, it can be inferred that songt can serve as an alternate means of instructing children in listening while simultaneously boosting their enthusiasm, particularly with regard to enhancing their listening comprehension, expanding their vocabulary, and refining their pronunciation. We believe that this finding will encourage language instructors to incorporate musical elements into their lessons, particularly when working with students from SMA N 2 Langowan, to improve their English language skills